Peripheral blood CD34+ cell monitoring after cyclophosphamide and granulocyte-colony-stimulating factor: an algorithm for the pre-emptive use of plerixafor - Farina, Lucia; Spina, Francesco; Guidetti, Anna; Longoni, Paolo; Ravagnani, Fernando; Dodero, Anna; Montefusco, Vittorio; Carlo-Stella, Carmelo; Corradini, Paolo (Leukemia & lymphoma, 2014)
Abstract Plerixafor "on demand" after chemotherapy plus granulocyte-colony-stimulating factor (G-CSF) is efficient in peripheral stem cell mobilization, but the timing of administration and criteria for patient selection are under investigation. To devise an algorithm for the "on demand" use of plerixafor at the first mobilization attempt, we analyzed the kinetics of hematopoietic recovery and peripheral blood CD34+ cells in 107 patients treated with high-dose cyclophosphamide plus G-CSF. Fifty-one patients with myeloma were treated with cyclophosphamide 3-4 g/m2 on day 0 followed by G-CSF 10 μg/kg from day + 6, and 56 patients with lymphoma received cyclophosphamide 6-7 g/m2 followed by G-CSF 5 μg/kg from day + 1. Peripheral blood CD34+ cell monitoring was started on day + 8 in patients with myeloma and day + 10 in patients with lymphoma. The outcome of interest was a collection of ≤ 2 × 106 CD34+/kg. By a multivariate logistic regression model, CD34+ cell count < 10/μL at leukocyte recovery (> 1000/μL) or leukocyte count < 1000/μL after day + 12 in myeloma and day + 14 in lymphoma predicted the failure of mobilization by 2.7 and 2.8 times (p = 0.001 and p = 0.02) with a sensitivity of 89% and specificity of 88%, respectively. Plerixafor "on demand" may be considered in patients with myeloma and lymphoma with delayed hematopoietic recovery and < 10/μL CD34+ cells, as a first-line mobilization strategy.